Kandungan Kalsium (Ca) dan Fospor (P) Silase Pakan Komplit Berbahan Dasar Jerami Jagung (Zea Mays) dengan Penambahan Azolla (Azolla pinnata) Sebagai Pakan Ternak Ruminansia - Muh. Iqbal Adi Putra Dahlan; Muhammad Jurhadi Kadir; Rasbawati Rasbawati (Fakultas MIPA UNM, 2022)
Abstract. This study aims to determine the calcium (Ca) and phosphorus (P) content of complete feed silage made from corn straw (Zea mays) with the addition of Azolla (Azolla pinnata) as ruminant animal feed. complete feed silage research used a completely randomized design (crd) with 4 treatments and 3 replications. The complete feed treatments applied in this study were: S1= 50% corn straw+30% azolla+19% rice bran+1% mineral mix, s2=50% corn straw+25% azolla+24% rice bran+1 % mineral mix, s3= 50% corn straw+20% azolla+29% rice bran+1% mineral mix, s4=50% corn straw+15% azolla+34% rice bran+1% mineral mix. The results of the analysis of variance showed that the calcium content of complete feed silage made from corn straw (Zea mays) with the addition of azolla at S1, S2, S3, S4 had no significant effect (P> 0.05), the average calcium (Ca) content of the feed was S1 (1.033%), S2 (1.036%), S3 (1.17%) and S4 (0.92%). Treatment S1 was not significantly different from the treatment S2, S3 and S4, S2 was not significantly different from S1, S3, and S4, S3 was not significantly different from S1, S2, and S4 and S4 was not significantly different from S1, S2, and S3. While the calcium content of complete feed silage made from corn straw (Zea mays) with the addition of azolla at S1, S2 and S3 had a significant effect (P<0.05). The average phosphorus content of feed is S1(1, %), S2(1.1%), S3(1.17%) and S4(1.03%). S1 treatment was not significantly different from S4 treatment and significantly different from S2 and S3, S2 was not significantly different from S3 and S4 and significantly different from S1, S3 was significantly different from S4 and S1 and not significantly different from S2, S4 was not significantly different from S1 and S2 but significantly different from S3. It was concluded that the addition of azolla (Azolla pinnata) at different levels to complete feed silage made from corn straw (Zea mays) did not significantly affect the calcium (Ca) content, but had a significant effect on the phosphorus (P) content. The best treatment in S3 with the addition of azolla (Azolla pinnata) 20%. Keywords: Azolla (Azolla pinnata), corn straw (Zea mays), calcium (ca) and phosphorus (p) content, complete silage